Analisis Online Impulse Buying dengan menggunakan Framework SOR - Syastra, Muhammad Taufik; Wangdra, Yvonne (Universitas Diponegoro, 2018)
Electronic commerce (e-commerce) transactions in a country must be continuously improved to support the country's economic development. E-commerce owner are looking for efforts / strategies to increase sales. The effort that can be done is to conduct an study of impulsive purchases online. The framework used to conduct this study is SOR (Stimulus, Organism and Response). The purpose of this study is to identify the factors causing impulsive purchases online and which factors that have the highest contribution. This study focuses on mainstream e-commerce websites such as: tokopedia, lazada, bukalapak, shopee, and elevenia. The number of respondents was 105 people. Data analysis techniques are Descriptive Analysis. To strengthen the data, the researchers conducted interviews with 10 respondents. The findings of this study are the factors causing impulsive purchases: (1) Promotion / discounts; (2) Flash sale; (3) Popular this week item; (4) Hot list product; (5) Payment installment facilities. Factors that have the highest contribution are Promo / discount with a value of 64.8%. Promos / discounts are the most influential an impulsive buying desire in conventional markets and e-commerce